Comparative analysis of the biological age of students at the Teachers' University - Н.М. Грибок; Р.О. Проць (H.S. Skovoroda Kharkiv National Pedagogical University, 2017)
Aim: To investigate the biological age of athletes and non-sports students. To carry out a comparative analysis of aging rates among representatives of both groups. Material and methods: the sample consisted of 58 male students: athletes (n = 28) aged 18-20 years and non-sports students (n = 30) aged 18-20 years. The group of athletes was represented by students of football, who were members of the team of the university for football and foot of the hall. All athletes had a sports qualification from the first adult class to the CM. The comparison was conducted with a group of non-sports students, except for physical education. The biological age was determined by the method of VP Voytenka (1991). Results: It was determined that the biological age of the examined sportsmen is 23.44 years (δ = 3.77), while the non-sports students are 38.82 (δ = 4.65). In absolute terms, the difference is 4.54 years for athletes and 20.32 for non-sports students. According to the relative indicator, the biological age of young footballers is 12, 4% higher than the passport. Conclusions: the pace of age-related changes in athletes is slowed down, and students not engaged in sports are accelerated. This is due to more harmful habits, low levels of motor activity. Such students are advised to adhere to the rules of healthy lifestyle, active rest, physical activity, sports.